Detecting the Carotenoid Pigmentation due to Haloarchaea Microbes in the Lonar Lake, Maharashtra, India Using Sentinel-2 Images - Bhattacharjee R.; Choubey A.; Das N.; Ohri A.; Gaur S. (My University, 2025)
The Lonar Lake of Maharashtra is a crater based-saline lake. During the month of June 2020, this lake suddenly changed its colour and turned to pink due to the presence of Haloarchaea microbes, and this species have a unique adaptation style to survive in high saline condition. The salinity of this lake is increasing due to less rainfall, low human intervention, and an increase in the temperature of this region. These microbes produce fantastic bloom, which can be sensed from outer space because of red–orange carotenoids production. In this work, Sentinel 2A datasets have been used for the duration of January 2020 to June 2020. These datasets have been processed in Google Earth Engine platform and several indices like Salinity Index, Surface Algal Bloom Index, and Normalized Difference Haloarchaea Index have been calculated. With the help of these indices, it has been found that the appearance of these microbes has happened in the early part of June 2020, and in more precise terms, it can be stated that between May 31 and June 5, these microbes have appeared in the lake. © 2020, Indian Society of Remote Sensing.